Substance Abuse Recovery in College Community Supported Abstinence - Cleveland, H. Harrington; Harris, Kitty S.; Wiebe, Richard P.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
More than 80% of college students are drinking. More than a third do drugs. For students struggling with substance abuse, temptations on campus$1 (Band stressors that can derail abstinence$1 (Brun high. In response, several colleges and universities offer effective support in the form of recovery communities, which are more appropriate to campus settings and young adult development than traditional 12-step groups alone. Substance Abuse Recovery in College explains in authoritative detail what collegiate recovery communities are, the types of services they provide, and their role in the context of campus life, with extended examples from Texas Tech University$1 (Bs influential CSAR (Center for the Study of Addiction and Recovery) program. Using data from both conventional surveys and end-of-day daily Palm Pilot assessments as well as focus groups, the book examines community members$1 (Bexperiences. In addition, the importance of a positive relationship between the recovery community and the school administration is emphasized. Topics covered include: The growing need for recovery services at colleges. How recovery communities support abstinence and relapse prevention. Who are community members and their addiction and treatment histories. Daily lives of young adults in a collegiate recovery community. Challenges and opportunities in establishing recovery communities on campus. Building abstinence support into an academic curriculum. This volume offers clear insights and up-close perspectives of importance to developmental and clinical child psychologists, social workers, higher education policymakers, and related professionals in human development, family studies, student services, college health care, and community services.s
The Need for College Recovery Services -- Collegiate Recovery Communities: What They Are and How They Support Recovery -- Facilitating Identity Development in Collegiate Recovery: An Eriksonian Perspective -- Characteristics of Collegiate Recovery Community Members -- Maintaining Abstinence in College: Temptations and Tactics -- Daily Lives of Young Adult Members of a Collegiate Recovery Community -- How Membership in the Collegiate Recovery Community Maximizes Social Support for Abstinence and Reduces Risk of Relapse -- Building Support for Recovery into an Academic Curriculum: Student Reflections on the Value of Staff Run Seminars -- Establishing College-Based Recovery Communities: Opportunities and Challenges Encountered.
Keywords: Philosophy (General).; Education, Higher; Social work; Applied psychology; Developmental psychology; Psychology; Child and School Psychology; Higher Education; Social Work; Psychotherapy and Counseling